Policy proposal for the agroindustrial development of the Caribbean Community (CARICOM) (Conformatica, S.A. de C.V. MX, 1993)
Seeks to assess and to draft policies to improve the performance of agroindustry for the community countries. Attempts to explain the international and regional macroeconomic setting. Provides an assessment of the farming sector and of agroindustry. Examines the outlook and the policies proposed for promoting agroindustry. Proposes policies that might have the greatest effect within the macroeconomic context of the countries of the region, given the present international setting. Reports on exploratory missions undertaken to Guyana, Trinidad and Tobago, Barbados, St. Lucia and Jamaica.
DC